Annual Report on the Working of State Electricity Boards Electricity Departments April, 2000 - Planning Commission (Planning Commission, 2000)
The pattern of sales to various sectors has undergone significant changes in the last few years. Figure 1.4 shows the sectoral consumption patterns for the years 1984-85, 1989-90 and 9189-97 The share of domestic and agriculture sectors in the total sales increased from 27.4% in 1984-85 to nearly 50% in 1998-99 while that of industry declined from over 50% to about 32% over the years. This has adversely affected the profitability of the SEBs because the tariff charged from agriculture and domestic sectors is lower than the cost of supply of electricity. The per capita electricity consumption increased from 178 Kwh in 1985-86 to 334 Kwh in 1996-97 i.e. an increase of about 90% in a decade
(Power & Energy Division) Planning Commission
(Power & Energy Division) Planning Commission